2005
DOI: 10.1021/jm050565b
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening of Novel CB2 Ligands Using a Comparative Model of the Human Cannabinoid CB2 Receptor

Abstract: To identify novel selective CB2 lead compounds, a comparative model of the CB2 receptor was constructed using the high-resolution bovine rhodopsin X-ray structure as a template. The CB2 model was utilized both in building the database queries and in filtering the hit compounds by a docking and scoring method. In G-protein activation assays, 1-isoquinolyl[3-(trifluoromethyl)phenyl]methanone (40, NRB 04079) was found to act as a selective agonist at the human CB2 receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
62
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 57 publications
5
62
1
Order By: Relevance
“…27 Therefore, this site was speculated to be the CB2 agonist binding pocket. The defined CB2 agonist binding pocket shows certain differences with the model reported by Salo et al 15 The correspondent structure-based database search results for novel CB2 agonist leads will be reported elsewhere, whereas the current study is mainly focused on developing a virtual screening protocol for a CB2 antagonist search.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…27 Therefore, this site was speculated to be the CB2 agonist binding pocket. The defined CB2 agonist binding pocket shows certain differences with the model reported by Salo et al 15 The correspondent structure-based database search results for novel CB2 agonist leads will be reported elsewhere, whereas the current study is mainly focused on developing a virtual screening protocol for a CB2 antagonist search.…”
Section: Resultsmentioning
confidence: 74%
“…In fact, the use of 3D GPCR structural models in drug design and structurebased virtual screening studies has increasingly emerged in recent literature. [6][7][8][9][10][11][12][13][14][15] Among these studies, it has been demonstrated that the homology models of dopamine D3, muscarinic M1, vasopressin V1a receptors, and 5HT 2c were reliable enough to retrieve known antagonists via structurebased virtual screening from several compound databases. 7,14 Rhodopsin-based homology models of the R 1A receptor could be used as the structural basis for the lead finding and optimization through the application of a hierarchical virtual screening procedure.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In some GPCR SBVS studies docking based screening simulations have been guided by pharmacophore constraints Evers and Klebe 2004;Sirci et al 2012). Pharmacophore models and/or exclusion constraints derived from structural models of receptor-ligand complexes (or the receptor alone) can be used as an alternative structure-based virtual screening approach to molecular docking simulations, as demonstrated in several successful GPCR SBVS campaigns to discover ligands of CA3R (Klabunde et al 2009), CNR2 (Salo et al 2005), FFAR1 (Tikhonova et al 2008), FPR1R (Edwards et al 2005), MCHR1 (Cavasotto et al 2008), HRH3 (Sirci et al 2012). …”
Section: Hierarchical Workflow For Gpcr Structure-based Ligand Discoverymentioning
confidence: 99%